Wages and Employment Growth: Disaggregated Evidence for West Germany - Jens Suedekum; Uwe Blien (European Regional Science Association (ERSA), 2004)
We address the effects of wages on employment growth on the basis of a theoretical model from which cost and demand effects can be derived. In the empirical analysis we take a highly disaggregated perspective and apply a newly developed shift-share regression technique on an exhaustive and very accurate data set for West Germany. The regression shows that the impact of regional wages on employment growth is significantly negative. There is some variation of this effect across sectors, but in no case we find support for the claim that an exogenous wage increase leads to higher employment growth. Keywords: Employment Growth, Shift-Share-Analysis, Regional Wages, Purchasing Power Argument. JEL- Classification: J23, E24, R11
Keywords: J23; E24; R11; 330; Employment Growth; Shift-Share-Analysis; Regional Wages; Purchasing Power Argument